A novel Nb2O5/Bi2WO6 heterojunction photocatalytic oxidative desulfurization catalyst with high visible light-induced photocatalytic activity. Issue 81 (2nd November 2017) - Wu, Jing; Li, Jian; Liu, Jin; Bai, Jin; Yang, Lina
Abstract : A novel Nb2 O5 /Bi2 WO6 heterojunction catalyst was synthesized and applied in PODS of DBT. It shows higher activity than pure Nb2 O5 and Bi2 WO6 in visible light induced PODS of DBT, in which holes and superoxide radicals are the main reactive species. Abstract : A novel Nb2 O5 /Bi2 WO6 heterojunction catalyst was successfully synthesized via a one-pot solvothermal process. The catalyst was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) with the corresponding XEDS energy mapping, UV-vis diffuse reflection spectra (UV-vis DRS), Fourier transform infrared (FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS). The photocatalytic oxidative desulfurization performances of the prepared samples were studied with DBT as the model sulfur compound under visible light irradiation. Results indicated that the Nb2 O5 /Bi2 WO6 exhibited considerably higher activity than pure Nb2 O5 and Bi2 WO6 and the desulfurization rate achieved 99% after visible light irradiation for 120 min. The catalyst also possessed good stability so that the desulfurization rate remained about 90% after seven cycle times and then the crystal structure of the catalyst has barely changed. Such enhanced photocatalytic activity is mainly attributed to the effective separation of photogenerated electron–hole pairs on Nb2 O5 /Bi2 WO6 heterojunction. Moreover, the synergistic effects of this photocatalytic oxidation and the extraction with the methanol as the solvent played an indispensable role in the desulfurization.